Perception of Local Community of Pinogu Toward Forest and Its Utilization - Diah, Diah Irawati Dwi Arini; Isdomo , Isdomo Yuliantoro (Forestry Department, University of Muhammadiyah Makassar, 2019)
This study was aimed to obtain the Pinogu local peoples’s perception of the forest for their lives and to identification of forest resources utilization. Pinogu is a Bogani Nani Wartabone National Park’s enclave. The research was conducted in 2017 at Pinogu Sub-district which included five villages there are Bangiyo, Pinogu Induk, Pinogu Permai, Tilongibila and Dataran Hijau. Data collected with survey method by interviewing 150 respondents from five villages. Data was analyzed using, Likert Scale, Kendall Tau Correlation test and descriptive qualitative. Overall, the results showed forest perception in Pinogu’s local peoples was in fairly good category with value 79.69 from 40 - 100 and influenced by position in village communities variable. The local peoples utilized the forest resources inculdes hard wood, rattan, medicinal plants, wild animals, forest fruits, forest mushrooms, honey. This forest resources obtained from the forests around Pinogu and inside area of Bogani Nani Wartabone National Park.